The Influence of Compensation, Work Environment, and Organizational Commitment on Employee Job Satisfaction at PT Giri Aneka Usaha (Perseroda) Wonogir Regency - Eko Wahyudi; Sri Wijiastuti; Zandra Dwanita Widodo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this research is to examine and measure both partially and simultaneously the influence of compensation, work environment and organizational commitment on employee job satisfaction. To find out the factors that have the most dominant influence on employee job satisfaction. This research was conducted on employees of PT Giri Aneka Usaha (Perseroda) Wonogiri Regency. In this study, the population was all employees of PT Giri Aneka Usaha (Perseroda) Wonogiri Regency, namely 71 employees. Considering that the population size in this study is not too large, the entire population in this study, totaling 71 employees, was taken as a sample. Thus, this research is a population/census research. The sampling technique uses saturated sampling. The research results found that both partially and simultaneously compensation, work environment and organizational commitment had a positive effect on employee job satisfaction. It was also found that compensation had the most dominant influence on employee job satisfaction. Job satisfaction of PT Giri Aneka Usaha (Perseroda) Wonogiri Regency employees is influenced by compensation, work environment and organizational commitment by 94.20%, while the remaining 5.80 is influenced by other variables outside this research model.